MODEL PENGABDIAN TERINTEGRASI UNTUK UMKM HIJAU: PELATIHAN BERBASIS LIMBAH, TRANSFORMASI DIGITAL, DAN DUKUNGAN PSIKOSOSIAL PADA SEBUKA - Erdina Indrawati; Maya Syafriana Effendi; Essy Malays Sari Sakti (Jurnal Abdi Insani, 2025)
This community service initiative aimed to strengthen the green entrepreneurship capacity of SEBUKA MSMEs through waste-based technical training, digital business transformation, and psychosocial empowerment. The program applied participatory methods, continuous mentoring, and evaluation using pre-test and post-test instruments. The results indicated a significant improvement in participants’ entrepreneurial perception (p = 0.003). Technical training enhanced eco-friendly production skills, digitalization expanded market access, while psychosocial support fostered greater confidence. These findings demonstrate that needs-based and collaborative interventions are effective strategies for empowering community MSMEs. Furthermore, the program contributes to the Sustainable Development Goals (SDGs), particularly in waste reduction and local economic empowerment.